(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper describes the process of engaging with a primary philosophical text, an essay by Heidegger – known for its difficult and esoteric language. It describes the struggle of understanding Heidegger’s complex philosophical ideas and the writer’s process of making these concepts explicit and relevant to psychotherapy. Two concepts aletheia (truth) and the clearing are explored in detail. The account takes the form of a phenomenological inquiry.